Fault Tolerance in Real Time Distributed System - Sharma, Gajendra; Yadav, Ankita (Review of Computer Engineering Research, 2018)
Fault tolerance is in the center of distributed system design that covers various methodologies. This research paper aims to investigate different types and techniques of fault tolerance which are being used in many real time distributed systems. The fault can be detected and recovered by many techniques. Moreover, an appropriate fault detector can avoid loss due to system crash or any kind of failure in system. This paper provides a framework for detecting fault in real time system which is supposed to be handled and processed further by the help of coordinator.